Triptycene End-Capped Quinoxalinophenanthrophenazines with Aromatic Substituents – Synthesis, Characterization, and Single-Crystal Structure Analysis - Ueberricke, Lucas; Wieland, Sonja; Rominger, Frank; Mastalerz, Michael (Organic Materials, 2019)
In a previous study, we found that one-fold triptycene end-capped quinoxalinophenanthrophenazines (QPPs) arrange in crystals preferably in a coplanar fashion providing high overlap of the π-planes. Thus, resulting in high calculated charge transfer integrals. Most interestingly, this motif was observed for a variety of QPPs derivatives, independently of the nature of their peripheral substituents, e.g. bromide, methoxy, cyano, or triisopropylsilylethynyl groups, and of the crystallization conditions. Here, we describe the synthesis of another small series of three QPPs containing different aromatic substituents at the same position to get an insight, whether these aromatic substituents disturb the otherwise preferred π stacking of the QPP planes.
Keywords: triptycenes; quinoxalinophenanthrophenazines; N-heterocycles; polycyclic aromatic compounds